Design and exploitation powerful thyratron swith in modulators accelerators NSC KIPT - Beloglazov, V.I.; Chaika, I.A.; Chertishchev, I.A.; Kaplij, D.A.; Kosoi, A.I.; Romas’ko, V.P.; Titov, V.Yu.; Tur, Yu.D.; Tsimbal, V.A.; Zaitsev, I.N.; Zaitsev, E.I. (Вопросы атомной науки и техники, 2016)
Modulators performed according to linear circuit with PFN depletion via pulse transformer are used in NSC KIPT active electron accelerators. Switch and its components determine the reliability of a plant. Hydrogen thyratrons providing the current switching up to 2.3 kA at anode voltage up to 40 kV are used as a switch in modulators of technological accelerators. The results of study of operational reliability of switches in active accelerators are reported in this article